2022
DOI: 10.22551/2022.34.0901.10201
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in thyroid autoimmune diseases

Abstract: The role of vitamin D in the human body is a complex one, proven by the many studies performed related to this aspect. Data from the literature on the correlation between vitamin D deficiency and thyroid autoimmune pathology, although present and increasing in the last 10 years, have failed to establish exactly whether or not there is a link between them. The aim of the study was to assess the status of vitamin D in patients with autoimmune thyroid disease; and to determine if there is a correlation between pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Recently published paper from Romania also showed results demonstrating that VD defi ciency was high in both AITDs and controls (67 % vs 72 %), which however was not statistically signifi cant (p = 0.464). These data are in agreement with our results and support our fi nding of high prevalence of VD defi ciency in AITDs but also in controls (14). In addition, the study of Kivity et al observed that the prevalence of VD defi ciency was similar between hypothyroid…”
Section: Discussionsupporting
confidence: 93%
“…Recently published paper from Romania also showed results demonstrating that VD defi ciency was high in both AITDs and controls (67 % vs 72 %), which however was not statistically signifi cant (p = 0.464). These data are in agreement with our results and support our fi nding of high prevalence of VD defi ciency in AITDs but also in controls (14). In addition, the study of Kivity et al observed that the prevalence of VD defi ciency was similar between hypothyroid…”
Section: Discussionsupporting
confidence: 93%